2011
DOI: 10.1016/j.bbadis.2010.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Essential role of neutrophil mobilization in concanavalin A-induced hepatitis is based on classic IL-6 signaling but not on IL-6 trans-signaling

Abstract: Neutrophil depleted mice are protected from concanavalin A-mediated hepatitis, showing that neutrophils are critical for cellular liver damage. Interleukin-6 has pro- and anti-inflammatory properties and mediates neutrophil recruitment in diseases such as rheumatoid arthritis. In classic signaling, interleukin-6 binds to the membrane-bound interleukin-6-receptor and initiates signaling via gp130. In interleukin-6 trans-signaling, the agonistic soluble interleukin-6-receptor can form a soluble interleukin-6/int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 34 publications
4
26
0
Order By: Relevance
“…In the present work we clearly demonstrated that the lack of IL-6 resulted in weaker inflammation (IL-6, IFNγ) and blunted acute phase response (SAP, HPTGN) in agreement with the known hepatotoxic effect of IL-6 in liver injury [23] and IL-6 involvement in leukocyte recruitment in liver disease [24]. Interestingly, other authors have suggested a hepatoprotective effect of IL-6.…”
Section: Discussionsupporting
confidence: 88%
“…In the present work we clearly demonstrated that the lack of IL-6 resulted in weaker inflammation (IL-6, IFNγ) and blunted acute phase response (SAP, HPTGN) in agreement with the known hepatotoxic effect of IL-6 in liver injury [23] and IL-6 involvement in leukocyte recruitment in liver disease [24]. Interestingly, other authors have suggested a hepatoprotective effect of IL-6.…”
Section: Discussionsupporting
confidence: 88%
“…sIL-6R binds to IL-6 with comparable affinity as the mbIL-6R (21); consequently, the complex of IL-6/sIL-6R can activate gp130, a membrane protein is ubiquitously expressed (2225). Activation of gp130 via the IL-6/sIL-6R complex is termed IL-6 trans-signaling pathway, whereas activation of gp130 via the mbIL-6R is named IL-6 classic signaling pathway (23, 2628). IL-6 trans-signaling represents an alternative to classic IL-6 signaling and permits IL-6 to modulate a broad spectrum of target cells [Figure S2 in Supplementary Material, quoted from Ref.…”
Section: Classic and Trans-signaling Pathway Of Il-6mentioning
confidence: 99%
“…Thus the involvement of IL-6 on facilitating wound healing must be also considered as a possibility, based on their stimulation of keratinocyte proliferation. It has also been evidenced that IL-6 favours the liver regeneration [23].…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 has pro-and anti-inflammatory functions and controls regenerative processes including wound healing and liver regeneration [23].…”
Section: Introductionmentioning
confidence: 99%